Naturally Degradable Photonic Devices with Transient Function by Heterostructured Waxy‐Sublimating and Water‐Soluble Materials. Issue 20 (4th September 2020) - Camposeo, Andrea; D'Elia, Francesca; Portone, Alberto; Matino, Francesca; Archimi, Matteo; Conti, Silvia; Fiori, Gianluca; Pisignano, Dario; Persano, Luana
Abstract: Combined dry–wet transient materials and devices are introduced, which are based on water‐dissolvable dye‐doped polymers layered onto nonpolar cyclic hydrocarbon sublimating substrates. Light‐emitting heterostructures showing amplified spontaneous emission are obtained on transient elements and used as illumination sources for speckle‐free, full‐field imaging, and transient optical labels are realized that incorporate QR‐codes with stably encoded information. The transient behavior is also studied at the microscopic scale, highlighting the real‐time evolution of material domains in the sublimating compound. Finally, the exhausted components are fully soluble in water thus being naturally degradable. This technology opens new and versatile routes for environmental sensing, storage conditions monitoring, and organic photonics. Abstract : The first examples of combined dry–wet transient devices in photonics are reported. Light emitting heterostructures and encoded optical labels based on sublimating nonpolar cyclic hydrocarbon substrates and water‐soluble polymer layers are realized and programmed for a mechanical disintegration after use.